They who say yes: Brechtian reflections on teaching practices of two female and one male teacher (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article analyzes artistic and pedagogical experiences with Bertolt Brecht’s Epic Theater, where critical distance and aesthetic estrangement play a central role. The study of these concepts fostered the production of an educational video, reflections on Brechtian elements in a university musical theater production, and the implementation and evaluation of a workshop-class that proposed the friction of one of his didactic plays with games from Augusto Boal’s Theater of the Oppressed. The lasting impact of Brecht’s work in teaching practices are fundamental to social transformation and the critical development of students, highlighting theater as a tool for reflection and change.
Keywords: epic theater; theater of the oppressed; performing arts practices; teaching practices; teaching-learning